China's responsibility for climate change : Ethics, fairness and environmental policy - Harris, Paul G. (Book collections on Project MUSE., 2011)
This book describes China's contribution to global warming and analyzes its policy responses, examinining China's practical and ethical responsibility from a variety of perspectives.